2019
DOI: 10.1177/1038416218790571
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging students to draw on work experiences when articulating achievements and capabilities to enhance employability

Abstract: Employability drives higher education policy yet despite the investment in developing "rounded" graduates, students experience difficulties in articulating their achievements and capabilities during graduate recruitment. The purpose of this research was to trial and evaluate a career development intervention aimed at drawing on work experiences when applying for graduate roles. Students (N = 136) from two contrasting disciplines, Business and Physiotherapy, and two institutions participated in a two-staged int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Despite indications of self-esteem and self-efficacy concepts overlapping (Judge et al., 2002), they are distinct and hence we recommend that a life-span study of general and social self-efficacy should be undertaken and compared with studies into self-esteem across the lifetime. As others note in studies of careers, self-efficacy and confidence (Das et al., 2014; Jackson & Edgar, 2019), there is also the issue of self-reporting of data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite indications of self-esteem and self-efficacy concepts overlapping (Judge et al., 2002), they are distinct and hence we recommend that a life-span study of general and social self-efficacy should be undertaken and compared with studies into self-esteem across the lifetime. As others note in studies of careers, self-efficacy and confidence (Das et al., 2014; Jackson & Edgar, 2019), there is also the issue of self-reporting of data.…”
Section: Discussionmentioning
confidence: 99%
“…Given the amount of time spent in the work environment, meaningfulness in work is an important aspect of working life (Rothmann & Welsh, 2013), and indicative of a more transactional perspective on the psychological contract. Moreover, according to Jackson and Edgar (2019), in the current work context there has been a shift from a relational employment relationship premised on loyalty and respect to a transactional employment relationship focused on an economic exchange.…”
Section: Neutral Leadersmentioning
confidence: 99%
“…Numerous authors define internship as an integral component of a student’s time at university as it provides an opportunity to prepare for the working world (Australian Government, 2016 ; Jackson, 2015 ; Jackson & Collings, 2018 ; Koppi et al, 2010 ; Lucas et al, 2009 ; McIlveen et al, 2011 ). Jackson and Edgar ( 2019 ) found that students are not confident at drawing on their internship experience to assist in applying for graduate roles, demonstrating the need for internship as a part of an integrated suite of activities to assist career development.…”
Section: Career Development Model To Support Undergraduate It Studentsmentioning
confidence: 99%
“…During their time at university, students need to identify and prepare for their chosen career path by navigating through a variety of experiences that align with their personal career goals. To do this students need to be able to manage their own career development, however Jackson and Edgar ( 2019 ) found that student engagement with career services and interventions during their time at university can often be poor. While a variety of career development models exist in the literature (Bandura, 1986 ; Crites, 1973 ; Farmer, 1985 ; Hackett & Betz, 1981 ; Holland, 1985 ; Lent et al, 1994 ; Parsons, 1909 ; Super, 1980 ), their application within the university curriculum is often varied (Watts, 2005 ).…”
Section: Introductionmentioning
confidence: 99%